KINERJA BADAN LINGKUNGAN HIDUP PROV.SULUT - TAIDI, DELLY (JURNAL ADMINISTRASI PUBLIK, 2013)
Abstrak : Environment Agency North Sulawesi governor is the element job aid in carrying out duties and functions of guidance , coordination and technical services in environmental management . To carry out the duties and functions set out policies / programs and activities undertaken . Issues to be addressed in this study is how the performance of the organization Environmental Agency of North Sulawesi in implementing the policy / program / activity has been established .This study uses qualitative methods . In this study , the performance is defined as the level of success or achievement of the implementation of the policy / program / activity has been established in the strategic planning of the organization . Level of performance or the success seen through five indicators , namely : effectiveness , efficiency , responsiveness , transparency , and accountability .Results showed : ( 1 ) the level of effectiveness achieved is well seen from the implementation of the program / activity has been established , and the level of realization or achievement of planned output targets , (2 ) the level of efficiency is better seen from the use of budget / funding and human resources ; ( 3 ) the level of responsiveness is better seen from the alignment of programs and activities adopted / implemented with environmental issues and the needs / interests of the community , (4 ) the level of transparency is seen both ease of access to the necessary information society , as well as the openness and clarity of information available or given , and ( 5 ) the level of accountability is a good views of accountability to the public or stakeholder institutions on the performance of the policy / program / activities undertaken or accomplished .Based on the results of these studies conclude that the performance of the Provincial Environmental Agency in carrying out its duties and functions related to the development , coordination and technical services in environmental management , showing good results . Conclusions based on these results it is suggested that , with the increasing environmental problems in North Sulawesi it should be anticipated by BLH with established programs / activities more and more effective . In this regard the budget / funding allocated to North Sulawesi BLH needs to be improved / added .Keywords : organizational performance , policies / programs / activities of environmental management